INNOVATION EDUCATION IN THE WRITING OF SCIENTIFIC PAPERS - Rostini, Deti; Rosa, Ade Tutty Rokhayati (Universitas Sebelas Maret, 2018)
Among the Development of teachers professionalism is in the ability to make scientific papers which is believed to improve professionalism and improve the quality of learning ,.Among the problems of elementary schools teachers in the focus areas is lack of understanding in the writing of scientific papers. Whereas professional teachers should be able to write scientipic papers. Among the causes are long willingness, ability, coaching . This study aims to provide news strategies /theories and improvements in the willingness and ability of teachers to write scientifics papers.mastery of methodology ,research design , practical ways,and tips for successful writing of scientific papers .Problem solving frameworks by holding a workshop.The methode Is qualitative analytic,descriptive designed through R & D . This reseach belongs to appropriate technology development of empowerment model and professionalism of teachers of elementary school in West Java.